Integrasi Kearifan Lokal dalam Penguatan Literasi Sains Fisika di Sekolah: Suatu Kajian Sistematis - Zahara, Laxmi; Sudatha, I Gede Wawan; Santosa, Made Hery; Suartama, I Kadek (Lembaga Bale Literasi, 2025)
This study aims to identify and analyze the forms and contributions of integrating local wisdom into physics learning to improve students' scientific literacy. The background of this review is the low level of scientific literacy in Indonesia, as indicated by the 2018 PISA data, highlighting the need for contextual approaches in education, including the use of local wisdom. The method used is a systematic literature review guided by the PRISMA framework, involving identification, screening, eligibility, and inclusion of articles from Scopus, ERIC, and Google Scholar databases for the 2020–2025 period. From 19,534 documents initially identified, 15 articles were selected for in-depth analysis. The findings reveal that the forms of local wisdom integration include traditional tools, cultural ceremonies, local foods, traditional houses, and social values, all connected to physics topics such as motion, heat, pressure, and energy. This integration has been proven to enhance students’ scientific literacy across four dimensions: cognitive (conceptual understanding), procedural (scientific skills), affective (attitudes toward science and culture), and contextual (ability to relate science to real-life situations). The findings affirm that local wisdom holds significant potential as a relevant and humanistic learning approach aligned with the principles of the Merdeka Curriculum. This review is expected to serve as a foundation for developing more systematic and applicable models of physics learning based on local culture at the secondary school level.